Short versus ‘Standard’ Scarf Osteotomy for Hallux Valgus Correction - Sultan N. Qasim FRCS (Tr & Orth); Jitendra Mangwani MBBS, MS, FRCS (Tr&Orth) (Foot & Ankle Orthopaedics, 2016)
Category: Bunion Introduction/Purpose: Scarf osteotomy is an established procedure for correction of hallux valgus deformity. The technique has evolved and is effectively used for all grades of deformities. Short osteotomy (short scarf/modified chevron) and single screw fixation is an effective option for correction of mild to moderate hallux valgus deformity leading to lesser soft tissue disruption, smaller scar and being cost effective. Aim of this study was to compare radiological parameters of hallux valgus correction by a ‘standard’ scarf osteotomy and 2-screw fixation with a short osteotomy and single screw fixation Methods: We performed a retrospective review of prospectively collected data. The cases were identified from theatre log. 37 consecutive patients, operated between January 2013 and December 2014, were included. All had mild deformity as defined by maximum pre-operative intermetartarsal angle of 13 degrees. 16(43%) had short osteotomy with single screw fixation (Group 1) and the remaining 21 (57%) had ‘standard’ scarf osteotomy with 2 screw fixation (Group 2). Preoperative and final postoperative weight bearing radiographs were independently reviewed by both authors. Radiological parameters assessed were Hallux Valgus Angle (HVA), Intermetatarsal Angle (IMA), Distal Metatarsal Articular Angle (DMAA) and Medial Sesamoid position.Sesamoid position was determined by dividing metatarsal head into three equal sections and recorded as more than 50% of medial sesamoid in a section. The three grades were 3(lateral), 2(central) and 1(medial).Both groups were comparable for distribution of age and pre-operative radiological measures. Mean duration of X-Ray follow up was 3 months (range 2-12). SPSS version 20 was used to perform statistical analysis. Results: Mean age of patients was 49 years +/- 13 years. Mean improvement in radiological measures in degrees was - HVA from 24.4 to 10.9 (Group 1) and 35.3 to 12.6 (Group 2), IMA 10.0 to 3.3 (Group 1) and 10.5 to 5.4 (Group 2), DMAA 8.5 to 5.4 (Group 1) and 10.9 to 5.8 (Group 2), Medial Sesamoid position changed from 3 to 1 for both groups. Wilcoxon Signed Rank test showed all these improvements to be significant. T-test showed that both groups were comparable, with no statistically significant difference, for improvements in all radiological parameters. Conclusion: Short osteotomy with single screw fixation is equally effective in correction of symptomatic mild hallux valgus deformity as compared to ‘standard’ scarf osteotomy with the advantage of a smaller scar, lesser soft tissue disruption. We believe it is also cost effective because of potential reduction in duration of surgery and the cost of the implant.